Optimization Parameter Design of SEPIC-Cuk Converter - abu bakar, afarulrazi bin (International Journal of Integrated Engineering, 2019)
This paper discusses the optimization parameters design of combined SEPIC-Cuk converter based on SEPIC and Cuk operation for dual output voltage polarities. The SEPIC-Cuk converter is designed to be operated in continuous conduction mode, the selection of passive components, i.e., inductor and capacitor are based on the switching frequency, the duty cycle and inductor current ripple. The range of duty cycle for buck operation is 0<D<0.5, meanwhile for boost operation, the duty cycle range is 0.5<D<1.The simulation and experimental results show a good agreement. Thus, the designed parameters of the converter are confirmed. The finding shows that during buck operation, the output voltages are +3.96 V and -3.96 V with duty cycle of 0.25 when the output voltage is 12 V. Meanwhile, during boost operation, the output voltages are +36 V and -36 V with the duty cycle of 0.75 when the output voltage is 12 V.